Dysbiosis is one of the risk factor for stroke and cognitive impairment and potential target for treatment. (February 2021) - Koszewicz, Magdalena; Jaroch, Joanna; Brzecka, Anna; Ejma, Maria; Budrewicz, Slawomir; Mikhaleva, Liudmila M.; Muresanu, Cristian; Schield, Pamela; Somasundaram, Siva G.; Kirkland, Cecil E.; Avila-Rodriguez, Marco; Aliev, Gjumrakch
Graphical abstract: Gut microbiome disequilibrium may result from non-modifiable factors (such as age) or modifiable factors, such as e.g. obesity, metabolic, cardiovascular and sleep disorders or lack of physical activity. All these are also known as creating risk for the development of stroke and cognitive impairment. Cognitive impairment may also develop after stroke due to cerebrovascular and neurodegenerative lesions. Considerable percentage of the patients develops post-stroke dementia. Some of the deleterious changes in the microbiota can be prevented by pharmacological and non-pharmacological methods. It can be admitted that the prevention actions directed to correct gut dysbiosis could be taken into account as the factor diminishing the risk of post-stroke cognitive impairment and other types of dementia. Highlights: Cognitive impairment may be caused by neurodegenerative or cerebrovascular diseases. Often these coexistence and exacerbate one another. Stroke and other cognitive impairment may be associated with the disequilibrium in the gut microbiota. Dysbiosis may result from obesity; metabolic, cardiovascular, and sleep disorders; or lack of physical activity. Some of the deleterious changes in the microbiota can be prevented by pharmacological and non-pharmacological methods. The beneficial effects of appropriate composition of microbiota may lead to the development of new strategies of treatment for the post-stroke cognitive impairment and other dementia. Abstract: More than 50 million people have various forms of cognitive impairment basically caused by neurodegenerative diseases, such as Alzheimer's, Parkinson's, and cerebrovascular diseases as well as stroke. Often these conditions coexist and exacerbate one another. The damaged area in post-stroke dementia may lead to neurodegenerative lesions. Gut microbiome functions like an endocrine organ by generating bioactive metabolites that can directly or indirectly impact human physiology. An alteration in the composition and function of intestinal flora, i.e. gut dysbiosis, is implicated in neurodegenerative and cerebrovascular diseases. Additionally, gut dysbiosis may accelerate the progression of cognitive impairment. Dysbiosis may result from obesity; metabolic disorders, cardiovascular disease, and sleep disorders, Lack of physical activity is associated with dysbiosis as well. These may coexist in various patterns in older people, enhancing the risk, incidence, and progression of cerebrovascular lesions, neurodegenerative disorders, and cognitive impairment, creating a vicious circle. Recently, it has been reported that several metabolites produced by gut microbiota (e.g., trimethylamine/trimethylamine N-oxide, short-chain fatty acids, secondary bile acids) may be linked to neurodegenerative and cerebrovascular diseases. New treatment modalities, including prebiotic and probiotics, may normalize the gut microbiota composition, change the brain-gut barrier, and decrease the risk of the pathology development. Fecal microbiota transplantation, sometimes in combination with other methods, is used for remodeling and replenishing the symbiotic gut microbiome. This promising field of research is associated with basic findings of bidirectional communication between body organs and gut microbiota that creates new possibilities of pharmacological treatments of many clinical conditions. The authors present the role of gut microbiota in physiology, and the novel therapeutic targets in modulation of intestinal microbiota Personalized therapies based on their personal genome make up could offer benefits by modulating microbiota cross-talk with brain and cardiovascular system. A healthy lifestyle, including pre and probiotic nutrition is generally recommended. Prevention may also be enhanced by correcting gut dysbiosis resulting a reduced risk of post-stroke cognitive impairment including dementia.